Orientasi masa depan pada pemain game online: Bagaimana peranan dukungan sosial dan self-esteem? - Nurlaili, Karina Nisfiani; Dyan Evita Santi; Aliffia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract Future orientation is a picture that is seen by individuals about themselves in the future. The research objective was to determine the relationship between social support and self-esteem towards the future orientation of online game players. The population of this research is online game players aged teenagers in Surabaya. There were 140 research participants who were taken by accidental sampling technique. The research instrument used a future orientation scale adapted from Nurmi (1991), a social support scale adapted from Sarafino (2012), and a self-esteem scale from Coopersmith (1967). Data analysis techniques in this study used the Spearman Rho technique. The results of the study show that there is a significant relationship between social support and future orientation and that there is a significant relationship between self-esteem and future orientation. Future researchers can consider other variables that influence future orientation, such as self-efficacy and gender. Keywords: future orientation, social support, self-esteem, game online players.